2006
DOI: 10.1155/2006/281315
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection of Disseminated Tumor Cells in the Peripheral Blood of Patients with Gastric Cancer: Evaluation of Their Prognostic Significance

Abstract: Early detection of disseminated tumor cells in the peripheral blood of patients with early stage gastric cancer could help to improve the outcome after tumor resection. The aim of this study is to evaluate the prognostic significance of tumor-related mRNA for the detection of circulating tumor cells in gastric cancer patients by a reverse-transcriptase polymerase chain reaction (RT-PCR) method. We simultaneously analyzed human telomerase reverse transcriptase (hTERT), cytokeratin-19 (CK-19), cytokeratin-20 (CK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
3
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 24 publications
(34 reference statements)
2
33
3
4
Order By: Relevance
“…With membrane array, we observed that the detection rates of using single markers for CTCs in GC patients ranged from 78.1% to 82.8%, apparently higher than the results with RT-PCR (61.9-78.6%) in our previous observation 25 or those in another investigation (35.5-51.6%). 13 This indicates that this highly sensitive, high-throughput method can serve as an appropriate tool for GC detection.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…With membrane array, we observed that the detection rates of using single markers for CTCs in GC patients ranged from 78.1% to 82.8%, apparently higher than the results with RT-PCR (61.9-78.6%) in our previous observation 25 or those in another investigation (35.5-51.6%). 13 This indicates that this highly sensitive, high-throughput method can serve as an appropriate tool for GC detection.…”
Section: Discussioncontrasting
confidence: 70%
“…We have demonstrated previously that RT-PCR of CEA mRNA marker was a highly sensitive approach for CTCs detection in GC patients. 25 Additionally, a panel of molecular markers could enhance the sensitivity for CTCs detection, compared with single markers in use. 21 RT-PCR assay is by far regarded widely to be the most sensitive method for detecting tumor-associated molecular markers.…”
Section: Discussionmentioning
confidence: 99%
“…CTC-positive rate based on CEA mRNA marker was well correlated with postoperative recurrence, tumor size, vascular invasion, depth of tumor invasion, lymph node metastasis, and TNM stage (Wu et al 2006). Earlier study got the similar data (Seo et al 2005).…”
Section: Gastric Cancermentioning
confidence: 57%
“…Other studies showed MUC1, CK20, and hTERT expressions in peripheral blood of healthy individuals (de Cremoux et al, 2000;Gradilone et al, 2003;Uen et al, 2006;Wu et al, 2006;Wang et al, 2007). Illegitimate transcription of tissue-specific genes in blood from healthy individuals has been previously described by the mononuclear fraction.…”
Section: Discussionmentioning
confidence: 83%